PERSPEKTIF HUKUM INDONESIA TERHADAP ANAK HASIL PERKAWINAN CAMPUR - Nilawati Nilawati (An Nisa'a, 2014)
Mixed marriage has penetrated all corners of the country and society class. Globalization of information, economy, education, and transportation has shed the stigma that mixed marriages are marriages between wealthy expatriates and people of Indonesia. According to a survey conducted by the Mixed Couple Club, introductory line that carries a different nationality married couples include introduction via the Internet, former coworkers, met while on vacation, a former school friend, and pen pals. Mixed marriages also occurred in the Indonesian migrant workers with labor from other countries. With lots of mixed marriages in Indonesia should have legal protection in mixed marriages are listed with both the legislation in Indonesia. ملخص : الزواج المختلط قد اخترقت كل ركن من أركان البلاد والمجتمع الطبقي. عولمة الإعلام والاقتصاد والتعليم، والنقل والتخلص من وصمة العار أن الزيجات المختلطة يتم الزواج بين المغتربين الأثرياء وشعب اندونيسيا. وفقا لمسح أجرته والمختلطة زوجين نادي، السطر الاستهلالي الذي يحمل جنسية مختلفة المتزوجين وتشمل مقدمة عن طريق شبكة الإنترنت، وزملاء العمل السابق / الأعمال التجارية، في الوقت الذي اجتمع يوم عطلة، وهو صديق سابق المدرسة / الكلية، والزملاء من ركلة جزاء. كما حدثت زيجات مختلطة في العمال المهاجرين الاندونيسيين مع العمالة من بلدان أخرى. مع الكثير من الزيجات المختلطة في إندونيسيا ينبغي أن تكون الحماية القانونية في الزيجات المختلطة المسرودة مع كل من التشريعات في اندونيسيا.